2015
DOI: 10.5152/tjar.2015.92668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ketamine, Thiopental and Ketamine–Thiopental Combination during Electroconvulsive Therapy for Depression

Abstract: Objective: We aimed to evaluate the effect of anaesthesia with thiopental (4 mg kg ) and ketamine− thiopental (1 mg kg −1 and 4 mg kg −1 , respectively) combination during electroconvulsive therapy (ECT) on the Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HAM-A) and haemodynamic variables in patients with resistant major depression. Methods:Patients with HDRS scores above 17 were included. The patients were randomly divided into three groups according to the anaesthesia used. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…We found a further six randomised trials not included in these meta-analyses. Four found no greater efficacy with ketamine,31, 33, 35, 36 and two reported greater efficacy in the ketamine-treated group,29, 37 although of these two studies, there is uncertainty about the statistical robustness in one 37 and the plausibility of the clinical responses seen in the other 29 . The study reported here found a small numerical advantage in the saline-treated group with the 95% confidence interval excluding more than small-to-moderate advantage with ketamine treatment.…”
Section: Discussionmentioning
confidence: 95%
“…We found a further six randomised trials not included in these meta-analyses. Four found no greater efficacy with ketamine,31, 33, 35, 36 and two reported greater efficacy in the ketamine-treated group,29, 37 although of these two studies, there is uncertainty about the statistical robustness in one 37 and the plausibility of the clinical responses seen in the other 29 . The study reported here found a small numerical advantage in the saline-treated group with the 95% confidence interval excluding more than small-to-moderate advantage with ketamine treatment.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a randomized, controlled trial of MDD patients who received pre-ECT ketamine (1–1.5 mg/kg at ECT sessions 2 and 3 or 1–1.5 mg/kg at ECT sessions 2, 4, 6, 8, 10) or thiopental (2–3 mg/kg for all ECT sessions) found that depressive symptom severity was lower after the last ECT session in the group that received ketamine prior to the five ECT sessions than in the group that received only thiopental for all ECT sessions [96], suggesting that a greater frequency of paired ketamine and ECT may offer more clinical benefit than a single pre-ECT ketamine infusion. In contrast, another study series compared pre-ECT infusions of ketamine (1 mg/kg), thiopental (4 mg/kg), or both agents; the investigators found that depression symptom scores improved for all groups (as assessed by the HAM-D) and no statistically significant differences were observed between groups [97]. In another study of 90 patients with TRD randomly assigned to receive either ketamine (0.8mg/kg), subanesthetic ketamine (0.5mg/kg) plus propofol (0.5mg/kg), or propofol (0.8mg/kg) prior to eight ECT sessions, those in the ketamine group had an earlier reduction in depressive symptoms; compared to the other two groups, this effect was most pronounced after completion of the second treatment and lasted until the last treatment [98].…”
Section: Glutamatergic Synergism and The Maintenance Of Ketamine’smentioning
confidence: 99%
“…Safety concerns in the setting of ECT include higher rates of hypertension, QTc interval prolongation, transient arrhythmias, confusion, or fear, with hallucinations upon awakening from anesthesia. 7 9 , 12 , 16 , 23 , 25 The rates of these effects appear to have a positive correlation with an increasing dose of ketamine, notably in the 0.8–2.0 mg/kg dosing range. 8 , 9 , 12 , 16 , 23 , 25 Ketamine use in patients with cardiovascular disease should be considered with caution, especially when used in an ECT setting.…”
Section: Discussionmentioning
confidence: 99%
“… 9 When combined with barbiturates such as thiopental, ketamine has not been shown to be effective in reducing depressive symptoms, likely due to the effects of barbiturates in attenuating seizures as a result of their anticonvulsant properties. 7 , 11 , 15 , 16 Ketamine may have a role as an adjunctive agent to a non-barbiturate anesthetic, or as a sole anesthetic to accelerate response in the severely ill and those at risk of suicide. While iv ketamine remains the main route of administration, a few studies have demonstrated promising results in non-ECT settings when using alternate routes, notably intranasal.…”
Section: Discussionmentioning
confidence: 99%